ASSOCIATION BETWEEN EMOTIONAL DEVELOPMENT AND BULLYING BEHAVIOR IN CHILDREN AT THE ELEMENTARY SCHOOL NO 7, BANYUASIN, PRAJIN, PALEMBANG - Sri Tirtayanti; Intansari Nurjannah; Lely Lusmilasari (Belitung Nursing Journal, 2017)
Background: Bullying is a form of repetitive persecution both on physical and emotional aggressions and potentially causing mental and physical disorders on perpetrators and victims. There are various factors that may affect a child to behave as bullies. These are important factors to be identified as one of prevention effort to stop bullying behavior on children. Objective: This research aims to identify the association between emotional development and bullying behavior in children at the Elementary School No 7, Banyuasin Prajin, Palembang, Indonesia. Methods: This was a correlation descriptive using a cross sectional design. This research has been conducted on November 21, until December 1, 2016 involving 85 children as respondents. The instruments used for this research were Bar-On Emotional Quotient Inventory: Youth Version, school-bullying questionnaire, parenting style questionnaire and peer influence questionnaire. Chi-square test was used for bivariate data analysis and logistic regression test for multivariate analysis. Results: Results from chi-square test showed a significant association between emotional developments and parenting with bullying behavior (ρ<0.05), but no significant correlation between peer influence and bullying behavior (ρ>0.05). Logistic regression test showed a significant relationship between parenting and bullying behavior (OR) 4.655 (95% CI: 1.292-16.774), which indicated that the uninvolved parenting potentially makes bullying behavior have a chance to increase 4.655 times higher. Conclusion: There is a significant association between emotional development and parenting with children bullying behavior.